Pemeriksaan Dan Penatalaksanaan Skabies Serta Edukasi Faktor Resiko di Panti Asuhan Baaiturrahmah Kabupaten Kampar - Dwi Lesmana, Suri; Afandi, Dedi; Mislindawati (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
Scabies is a parasitic disease that is still a health problem today. Scabies has symptoms of itching that can affect the entire body which will certainly disrupt the activities of the affected individual. This parasitic infection can easily spread to people around them through direct contact or other media such as clothing and other shared equipment. Kampar is one of the districts in Riau Province with a high incidence of scabies. Kampar Regency is a district in Riau Province which is a coastal area, in this case located on the coast of the Kampar River. Baiturrahmah Rimbo Panjang Orphanage is an orphanage located in Kampar Regency with poor sanitation and hygiene conditions and a fairly dense number of residents. Hygiene, sanitation and housing density are risk factors for contracting scabies. In this community service activity, scabies examinations will be carried out, treatment and education will be provided to the residents of the orphanage. It was found that there was an incidence of 43.7% of scabies cases in nursing home residents with the highest number of cases being males at 71.14%. From the evaluation of the level of knowledge, it was found that the level of knowledge increased after the education was carried out. In this activity, all residents were given treatment with 5% Permethrin, who were previously given an explanation of how to administer the drug.